Evaluation of the cutting tool wear rate using roughness and optical techniques - Bajaba, Nasser S. (Edelweiss Applied Science and Technology, 2025)
This study addresses the wear that occurs in cutting milling tools when they are operated for extended periods on various types of materials. The aim of this study is to measure the wear in these tools due to stress, high temperatures, and other factors such as aging, improper use, and unbalancing during operation. The methods employed include optical techniques using a digital microscope, which captures precise photos before and after use. The second method involves measuring the roughness of the surfaces of the cutting edges of these tools. It was found that the roughness values of the cutting edges vary after specific working hours; the roughness values decrease after operation. For carbide tools, the roughness decreased by 5%, while for HSS tools, it decreased by about 25% under the same operating conditions.